Discovery of a novel HIV -1 integrase inhibitor binding site: Insight into enzyme structure/function and inhibitor design - Al-Mawsawi, Laith Qassim (ProQuest Dissertations & Theses, 2007)
HIV-1 integrase (IN) is an essential enzyme for viral replication and the subject of extensive pharmacological research aimed at designing clinically suitable drugs for the treatment of HIV/AIDS. The viral enzyme catalyzes a DNA ‘cut and paste’ reaction resulting in proviral DNA integration into the host cell genome. These reactions are referred to as 3’-processing and strand transfer. Here we present the identification of an inhibitor binding site that represents the first allosteric inhibitor binding site identified for IN. The rational design of drugs targeting this site has the potential to exhibit two simultaneous mechanisms of action: the disruption of IN multimerization and the disruption of the LEDGF/p75-IN interaction, which is an essential IN cellular cofactor for viral replication. The identification of the inhibitor binding site has led to further studies that have uncovered critical biological aspects concerning the relationship between HIV-1 IN structure and function. Our studies have provided evidence of a mechanistic dissimilarity between both IN reactions, although the enzyme utilizes one active site. Additionally, we have uncovered a non-covalent π electron orbital interaction at the dimeric interface of the viral enzyme that is essential for viral replication. The π interaction is critical for the strand transfer activity of IN, but not 3’-processing. Lastly, we have demonstrated the biological activity of a LEDGF/p75 derived peptide, the study of which has provided further insight into IN biology.